A hybrid encryption system for communication and financial transactions using RSA and a novel symmetric key algorithm - Prakash Kuppuswamy; Saeed Qasim Yahya Al Khalidi Al-Maliki; Rajan John; Mohammad Haseebuddin; Ahmed Ali Shaik Meeran (Bulletin of Electrical Engineering and Informatics, 2023)
Today's digital data transmission over unsecured wired and wireless communication channels is making encryption algorithms an increasingly important tool for securing data and information. Hybrid encryption techniques combine encryption schemes of either two symmetric keys or both symmetric and asymmetric encryption methods, and that provides more security than public or private key single encryption models. Currently, there are many techniques on the market that use a combination of cryptographic algorithms and claim to provide higher data security. Many hybrid algorithms have failed to satisfy customers in securing data and cannot prevent all types of security threats. To improve the security of digital data, it is essential to develop novel and resilient security systems as it is inevitable in the digital era. The recommended algorithm scheme is a combination of the well-known Rivest Shamir Adleman (RSA) algorithm and a simple symmetric key (SSK) algorithm. The aim of this study is to develop a better encryption method using RSA and a newly proposed symmetric SSK algorithm. We believe that the proposed hybrid cryptographic algorithm provides more security and privacy.